دراسة تحليلية ميكانيكية حيوية بطريقة العناصر المنتهية لكسور الفك السفلي. - خليل, عبد الكريم; خفيف, خضر; عطية, أمجد (Latakia University Journal -Medical Sciences Series, 2019)
The aim of this study is to develop a new approach to the biomechanical behavior of the mandible when sustaining a single impact. Using MIMICS software, we built a 3D model of 32 years old man`s mandible. We obtained CT scan data necessary for the build from Tishreen university hospital. Then, The 3d model was exported to 3-MATIC software for meshing. Then, the mesh was exported to ANSYS software for analyzing using finite element method. Virtual loads were applied at three sites in the mandible: symphysis, parasymphysis and the body. The results showed concentrations of stress at the mandible neck in the first two case. In third body case, the stress concentrations were along the body. This study showed the mandible neck is an inherited weak point and a biomechanical defense mechanism which absorb the applied forces, protecting the brain in the medium cranial fossa.